2010
DOI: 10.1039/c0cc00646g
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridyl β-diketonate complexes: versatile polydentate metalloligands for metal–organic frameworks and hydrogen-bonded networks

Abstract: The Group 13 metal complexes [M(L(2))(3)], where M is Al or Ga and L(2) is 1,3-di(4-pyridyl)-1,3-propanedionato, are hexatopic metalloligands that have been used to prepare mixed-metal-organic frameworks containing interpenetrated primitive cubic networks. In contrast, the europium complex [Eu(HL(2))(3)(H(2)L(2))]Cl(4) x EtOH forms a hydrogen-bonded network following partial protonation of the pyridyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…This was confirmed in reports about the coordination chemistry of the mono-pyridyl ligands a [10][11][12][13][14] and b, 15 and of the di-pyridyl derivative c. 16, 17 3-IJ4-Pyridyl)acetylacetone (Scheme 1, a) has also been employed in halogen-and hydrogen-bonded extended structures. In addition, the pyridine derivatives in Scheme 1 (ligands a-c) behave as good N nucleophiles to metal cations.…”
Section: Introductionsupporting
confidence: 57%
“…This was confirmed in reports about the coordination chemistry of the mono-pyridyl ligands a [10][11][12][13][14] and b, 15 and of the di-pyridyl derivative c. 16, 17 3-IJ4-Pyridyl)acetylacetone (Scheme 1, a) has also been employed in halogen-and hydrogen-bonded extended structures. In addition, the pyridine derivatives in Scheme 1 (ligands a-c) behave as good N nucleophiles to metal cations.…”
Section: Introductionsupporting
confidence: 57%
“…Eu(Hdppd)3 (H 2 dppd)]Cl 4 ·EtOH reported earlier,16 reveal it is possible to coordinate between two and four dppd or dmppd ligands to a metal centre, depending on the size and coordination preference of the metal centre, though the reaction conditions also have a significant effect on the product isolated from the reaction. Although, at first sight, the ligands might appear to be relatively rigid, there is considerable flexibility in theirconformations, evidenced largely by the wide range of fold angles observed as a consequence of bending about the ligand O!!…”
mentioning
confidence: 82%
“…14,15 We recently communicated the use of the 1,3-di(4-pyridyl)propane-1,3-dionato ligand (dppd) to prepare the octahedral complexes [Al(dppd) 3 ] 3 and [Ga(dppd) 3 ]. 16 These compounds are metalloligands containing six exotopic pyridyl groups, so have the potential to act as octahedral nodes. We demonstrated that reaction of these complexes with silver(I) nitrate gave [Ag 3 M(dppd) 3 ](NO 3 ) 3 !xDMSO (M = Al, Ga), in which the silver centres bridge between metalloligands leading to interpenetrated cubic networks.…”
Section: Introductionmentioning
confidence: 99%
“…Geometric considerations apart, their inequivalent donor sites may favor the coordination of different metal centers: acetylacetone derivatives with N donor substituents combine coordination sites of different Pearson hardness (Pearson, 1997): 3-cyano-2,4-pentanedione ( Fig. 1, left; HacacCN; Burrows et al, 2007;Kondracka & Englert, 2008;, 1,3-di(pyridyl)acetylacetones (Burrows et al, 2010(Burrows et al, , 2012) and 3-(4-pyridyl)-2,4-pentanedione (Fig. 1, right;HacacPy;Mackay et al, 1995;Vreshch et al, 2003Vreshch et al, , 2004Vreshch et al, , 2005Chen et al, 2004;Zhang et al, 2008;Li et al, 2011; represent candidates for the engineering of extended structures.…”
Section: Introductionmentioning
confidence: 99%